(3OhQ GdJhGab GdYUHj GdYVdj ddCWQGa GdSadjI aj JWhjQ ObI hbhI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20(3SfI OQGSI ejOGfjI Ydi GfOjI GJMGO YfGHI h MeQGA YfGHIs - (3HhdYHGjR, YHO GdUeO s; (3RYHhH, LeGds; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3JgOa GdOQGSI Edi eYQaI OhQ GdJhGab GdYUHj GdYVdj ddCWQGa GdSadjI aj JWhjQ ObI hbhI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20(3SfI, hdJMbjb gPG GdgOa dLC GdHGMK Edi eYQaI GdYdGbI Hjf GdJhGab GdYUHj GdYVdj ddCWQGa GdSadjI aj JWhjQ ObI hbhI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20(3SfI, ef NdGd MSGH eYGed GdGQJHGW, Ke GdHMK Yf fSHI eSGgeI GdJhGab GdYUHj ddCWQGa GdSadjI aj JWhjQ ObI hbhI GdJUhjH dOi dGYHj cQI GdbOe ef NdGd MSGH eYGed GdJMOjO(B. (3HYO WQM GdaQVjI GdQFjSjI ddOQGSI GdJj Jbhd JhLO YdGbI PGJ OdGdI EMUGFjI Hjf GdJhGab GdYUHj GdYVdj ddCWQGa GdSadjI aj JWhjQ ObI hbhI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20(3SfI MjK GNJQfG YjfI GdOQGSI HGdWQjbI GdbUOjI, hbO hbY GNJjGQ GdHGMK Ydi dGYHj cQI GdbOe CcHQ ef (B20 (3SfI dfGOj MeQGA YfGHI, hfGOj GJMGO eOjfI YfGHI, h bGe HEJHGY GdefgL GdhUaj dedGAeJg dWHjYI hehVhY GdHMK(B. (3hJe GdGYJeGO Ydi GdGNJHGQGJ cCOGI ddbjGS, hbSeJ Edi(B: (3GNJHGQGJ HOfjI dbjGS eSJhi GdJhGab GdYUHj GdYVdj ddCWQGa GdSadjI Ydi GdfMh GdJGdj(B: (3EP Je JWHjb GNJHGQ GdbaR GdYehOj SGQLfJ JGSJ dbjGS eSJhi GdbhI GdGfaLGQjI ddCWQGa GdSadjI, hGNJHGQ adGejfZh dbjGS eSJhi GdJhGRf ef GdKHGJ, hGNJHGQ GdOhGFQ GdeQbeI dbjGS eSJhi GdJhGab Yjf bOe, hGNJHGQGJ JbfjI dbjGS ObI hbhI GdJUhjH, MjK Je JWHjb GNJHGQ GdMHGd dhQfQ fdSf dbjGS ObI GdJUhjH dOi dGYHj cQI GdbOe, hGNJHGQ GdJUhjH dCHYO eSGaI eecfI dbjGS bhI GdJUhjH(B. (3aj EWGQ GdOQGSI hWHjYJgG, hef NdGd GdaQVjGJ hGdefgL GdeJHY hGdeYGdLI GdEMUGFjI ddHjGfGJ hGdfJGFL GdeMbbI , hHYO YQVgG hefGbTI GdYdGbI GdGQJHGWjI Jecf GdHGMK ef EKHGJ aQVjI GdHMK GdQFjSjI hGdJhUd Edi GdGSJfJGL GdJGdj(B:(3JhLO YdGbI PGJ OdGdI EMUGFjI Hjf GdJhGab GdYUHj GdYVdj ddCWQGa GdSadjI hbhI hObI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20 (3SfI(B. (3aQVjGJ GdHMK GdJj cGfJ fbWI GfWdGb aj gPg GdOQGSI Hcd eLGdGJgG GdfXQjI h GdejOGfjI hHYO GdbjGe HELQGA GdGNJHGQGJ GdejOGfjI hefGbTJgG hJMdjdgG JhUd GdHGMK Edi JMbjb aQVjGJ GdHMK GdLRFjI GdJj JfU Ydi (B: " (3hLhO YdGbI PGJ OdGdI EMUGFjI Hjf GdbhI GdGfaLGQjI ddCWQGa GdSadjI hbhI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20 (3SfI(B. " (3hLhO YdGbI PGJ OdGdI EMUGFjI Hjf GdbhI GdGfaLGQjI ddCWQGa GdSadjI hObI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20 (3SfI(B. " (3hLhO YdGbI PGJ OdGdI EMUGFjI Hjf GdJhGRf hbhI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20 (3SfI(B. " (3hLhO YdGbI PGJ OdGdI EMUGFjI Hjf GdJhGRf hObI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20 (3SfI(B. " (3hLhO YdGbI PGJ OdGdI EMUGFjI Hjf GdJhGab Yjf bOe hbhI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20 (3SfI(B. " (3hLhO YdGbI PGJ OdGdI EMUGFjI Hjf GdJhGab Yjf bOe hObI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20 (3SfI(B. (3h bO NdU GdHGMK Edi GdfJjLI GdfgGFjI GdJj Jbhd (B: (3Ef ddJhGab GdYUHj GdYVdj ddCWQGa GdSadjI OhQ aj JWhjQ ObI hbhI GdJUhjH dOi dGYHj cQI GdbOe Ufa CcHQ ef (B20 (3SfI(B. s
(3OcJhQGIs
Keywords: (3GdCWQGa GdSadjIs; (3GdJMVjQ GdHOfj GdQjGVjs; (3GdJhGab GdYUHj GdMQcjs; (3cQI GdbOes